Things We Own Together: Sharing Possessions at Home - Gruning, Jane; Lindley, Siân (Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems, 2016)
Sharing is an important facet of human relationships, yet there is a lack of research on how people share ownership of possessions. This paper reports on a study that investigates shared ownership of physical and digital possessions through interviews with couples and families in 13 households. We offer a more nuanced definition of shared ownership and show that certain practices, which are central to sharing physical objects, are not supported in the sharing of digital content. We suggest potential approaches to address this, focusing in particular on how the sharing of possessions plays a role in the building of relationships and is done against a backdrop of trust.